Glioblastoma Tumours: Complex Challenges and Deadly Outcomes - Kilian, Alexandra (The Meducator, 2016)
Glioblastoma (GBM) tumours are the most common primary brain tumours among adults, with many treatment challenges. In addition to being highly malignant and fatal tumours, GBMs are also heterogeneous in tissue and genetic composition, difficult to target, frequently recurring and often treatment-resistant. As a result of these challenges, GBM treatment has been essentially unchanged for decades, with minute improvements in patient prognosis, despite active research efforts. Currently, patients have a mean survival time of less than fifteen months. This article aims to explore the current questions in GBM research, including the role and limitations of surgery and chemotherapy treatments, the relationship between age and prognosis, and the controversy surrounding the optimal extent of resection. Additionally, this article outlines the impact of notable research developments in the field, including the role of nanotechnology in the first successful chemo-radiotherapy treatment on otherwise treatment-resistant GBM cells.